Implementation of ICT Management to Improve Education Quality: A Case Study at Madrasah Aliyah Negeri (MAN) 2 Bandung City - Saifi, Ani Fatimah Zahra; Susilawati, Erni; Komala, Euis; Erihadiana, Mohamad (GoAcademica Research & Publishing, 2023)
The growth of technology has changed the way we learn and teach. The use of ICT in education has great potential to improve the efficiency, accessibility and quality of learning. Various challenges in the education sector, such as access gaps, unequal quality, lack of resources and curricula that do not always keep up with technological developments can be resolved with appropriate ICT management strategies. Studies on the level of technology adoption in various educational institutions, be they schools, colleges or training centers can provide insight into how effective the use of ICT is in improving the quality of education. This research uses descriptive methods and data collection is carried out using an assessment of primary data sources and secondary data sources. Because the collection and analysis of qualitative research data used in this research is interactive, the researcher interacted with the data sources above by conducting observations, interviews and literature reviews. The results of this research are that ICT planning in MAN 2 Bandung City includes vision and mission, ICT strategy and financing. Organizing ICT at MAN 2 Bandung City includes the infrastructure provided by the madrasah along with the human resources who manage this infrastructure. The implementation of ICT at MAN 2 Bandung City includes the implementation of ICT in learning and educational services. ICT evaluations are carried out regularly monthly by the Head and Deputy Head of the Madrasah and annually at work meetings. The quality of education at MAN 2 Bandung City can be seen from the increasing public interest in enrolling their children in school at this madrasa and from the number of graduates who continue their studies at both state and private universities.